ANALISIS KETERBUKAAN IDENTITAS HOMOSEKSUAL DALAM PERSPEKTIF HAM DI INDONESIA (Studi Fenomenologi Anggota Pria Homoseksual Organisasi LGBT Suara Kita) - Fikriyah Nurshafa (2022)
Discrimination against homosexual minority groups often occurs in Indonesian society. The impact of this discrimination makes homosexual individuals unable to be open about their sexual identity, like society in general. This study aims to describe the process of disclosing the sexual identity of homosexual male members of the LGBT organization Suara Kita in the perspective of human rights in Indonesia. This study uses Queer Theory which assumes that a person's sexual and gender identity cannot be categorized by the general understanding of society. Sexual and gender identities are formed based on the construction of social reality experienced by each individual. The research paradigm used is constructivism, with qualitative research methods and a phenomenological approach. Researchers used data collection techniques in the form of in-depth interviews with six homosexual male members of Suara Kita. The results show that the openness of homosexual identity is influenced by personality factors, interlocutors, gender, group size, topic of conversation, and finally discrimination factors that have been experienced. The six homosexual individuals in this study had experienced acts of discrimination because their sexual orientation was different from the general public. Acts of discrimination that have been experienced, namely bullying, negative stigma, death threats, sexual harassment, and physical violence Keywords: Homosexual, LGBT, Queer Theory, Discrimination, and Human Rights in Indonesia.